Selection and preparation of arable land for the organization of intensive mulberry trees in the scheme of planting 0.9x0.2 m from mulberry seedlings in the climatic conditions of Surkhandarya region - Khamzaev Temur Yigitalievich; Bobomurodov Murodjon Khojimurotovich; Mamatraimov Kamoliddin Turgun o’g’li; Karshieva Adolat Rahim qizi; Javliev Sherzod Rakhmatullaevich (International Journal on Human-Computing Studies, 2021)
Provides information on agronomic techniques of intensive mulberry care in the scheme of planting mulberry seedlings 0.9x0.2 meters, crop rotation of mulberry-alfalfa, the order of planting seedlings in autumn or spring